ENCOURAGING BREAST-FEEDING IN PRIMARY CARE HEALTH UNITSIN SANTA MARIA-RS - Ruth Maurer da Silva; Hedionéia Maria Foletto Pivetta; Eilamaria Libardoni Vieira; Amara Lúcia Holanda Tavares Battistel; Michelle Gracioli; Rosiana Cordeiro Righi (Universidade Federal do Paraná, 2007)
The act of breastfeeding until six months old, is an efficient method not only to meet nutritionist, immunologist,psychological aspects or babies' development, but also it is equally beneficial to mothers, strengthening mother/child's bond. Thestudy aimed to stimulate breastfeeding in Primary Care Health Units in the western region of Santa Maria-RS/Brazil, through weeklymeetings with groups of pregnant women, following the instructions recommended by the Breastfeeding- Friendly Primary Care UnitInitiative, founded on breastfeeding promotion, protection and support. Professors and academics of the Health Area, that is, fromNursing, Occupational Therapy, Nutrition and Physical Therapy from Centro Universitário Franciscano (UNIFRA), had developed aproject, in partnership with professionals from the Municipal Health Secretary, objectifying to decrease early weaning and makebreastfeeding an ongoing practice.